Silent spontaneous posterior uterine rupture of a prior caesarean delivery at 36 weeks of gestation - Shao Hui Chen; Xiu Ping Du (BMC, 2019)
Abstract Background In caesarean section patients, the spontaneous rupture of the posterior wall of the uterus is extremely rare, with nonspecific signs and symptoms being present. Perinatal and maternal morbidity and mortality are high. Case presentation A 28-year-old woman at 36 + 6 weeks of gestation presented with mild uterine contractions and developed a sudden abdominal distension. An emergency laparotomy was performed, and the posterior wall of the uterus had ruptured. A baby boy was born. Conclusion Silent uterine rupture is very rare and easy to ignore due to nonspecific clinical symptoms, unexplained haemoglobin reduction and haemoperitoneum, but these features caution us to more closely consider uterine rupture in patients.